ANALISIS EKONOMI PETERNAKAN AYAM BROILER DI KOTA PEKANBARU - Sri Ayu Kurniati; Sisca Vaulina (UIR Press, 2021)
Broiler farms have the potential to be developed but there are obstacles such as fluctuations in input and output prices, capital problems, and various production risks that will have a big impact on production yields. The purpose of the study was to determine the economic analysis of broiler farming in Pekanbaru City. The study used a survey method on 80 farmers in the Districts of Rumbai, Rumbai Pesisir, and Tenayan Raya. Data were analyzed descriptively, qualitatively and quantitatively and used BEP and MOS. The results showed that the total cost of production was IDR 80,431,995 with the highest variable cost for purchasing DOC. Revenue received was IDR 206,200,750 and was obtained from the sale of live chickens. The chicken manure was used as organic fertilizer. The profit value was IDR 125,768,755 and the R/C ratio was 2.56. The results showed that the business is feasible to be continued and developed. The BEP unit was 586 chickens with a price of IDR 331 and revenue of IDR 13,860,393/kg. For the chicken manure, the unit BEP value was 990 kg with price of IDR 23 and revenue of IDR 237,780. The MOS value for broiler farming is in the high category, so it is still within the safe limit.